2008
DOI: 10.1111/j.1365-2516.2008.01766.x
|View full text |Cite
|
Sign up to set email alerts
|

α2‐Antiplasmin and its deficiency: fibrinolysis out of balance

Abstract: Summary. Fibrinolysis serves an important role in the process of coagulation, ensuring that clots that are formed in response to injury resolve after the injured tissue is repaired. Fibrinolysis occurs because the protein plasminogen is converted to the active serine protease plasmin by its activating molecules (primarily tissue plasminogen activator). One of the inhibitors of fibrinolysis is a 2 -antiplasmin, which acts as the primary inhibitor of plasmin(ogen). Congenital deficiency of a 2 -antiplasmin cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(96 citation statements)
references
References 42 publications
1
92
0
3
Order By: Relevance
“…Discussion α 2 -AP is a serine protease inhibitor that rapidly sequesters plasmin into a stable inactive complex and thereby regulates fibrinolysis [17,18]. However, Kawashita et al reported that α 2 -AP also enhances dendritic growth in hippocampal neurons independently of the fibrinolytic system [24].…”
Section: Role Of Erk1/2 and P38 Mapk In α 2 -Ap Activitymentioning
confidence: 97%
See 2 more Smart Citations
“…Discussion α 2 -AP is a serine protease inhibitor that rapidly sequesters plasmin into a stable inactive complex and thereby regulates fibrinolysis [17,18]. However, Kawashita et al reported that α 2 -AP also enhances dendritic growth in hippocampal neurons independently of the fibrinolytic system [24].…”
Section: Role Of Erk1/2 and P38 Mapk In α 2 -Ap Activitymentioning
confidence: 97%
“…Plasmin inhibition by α 2 -AP is almost instantaneous, and leads to the formation of a stable inactive complex [17]. Significant bleeding tendency is observed in patients with homozygous α 2 -AP deficiency, highlighting its physiological significance [17,18]. Heterozygous patients have mild or no bleeding tendency [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the results published by Holmes and Wallace [7] evidence the significant dynamic decrease of α 2-AP activity closer to delivery, which is in agreement with our results. It is interesting to note that inherited and acquired α2-AP deficiency is associated with severe bleedings due to uncontrolled hyperfibrinolysis [97].…”
Section: Partmentioning
confidence: 99%
“…Heterozygous patients can have bleeding in response to trauma, surgery, or dental procedures or can be asymptomatic. 93,98 Intramedullary hematomas of long bones, which can occur without a history of trauma, are an unusual feature of homozygous AP deficiency. 99,100 Similar lesions have been seen in patients with afibrinogenemia.…”
Section: Defects Of Fibrinolysismentioning
confidence: 99%